EMPOWERING MSMEs IN INDRAMAYU REGENCY THROUGH WEBSITE BUILDER UTILIZATION AS A BRANDING STRATEGY FOR MARKET EXPANSION - Nida, Ria Rahma; Suhendry, Bayu; Atmadja, Ferry Setyadi; Riyantie, Mayang (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2025)
This community engagement initiative addressed digital transformation challenges among rural Micro, Small, and Medium Enterprises (MSMEs) in Indramayu, where only 30% utilized digital tools despite contributing significantly to Indonesia's economy (Dinas Koperasi Indramayu, 2023). The program provided hands-on training in website development using Wix and WordPress platforms, coupled with mentoring sessions for 30 selected MSMEs. Implementation followed three key phases: (1) digital needs assessment through community surveys, (2) practical workshops on website creation and digital marketing tools, and (3) individualized business mentoring. Post-intervention evaluation revealed that 93.3% of participants successfully established functional business websites, with 85% integrating Google My Business. Participating enterprises reported an average 25% sales increase and expanded market reach, including international orders for 50% of businesses. The initiative achieved multiple sustainable development outcomes: creating 10 digitalrelated jobs (SDG 8), establishing a replicable digitalization model (SDG 9), and reducing rural-urban disparities (SDG 10). Key challenges included internet connectivity issues (affecting 20% of participants) and requests for ongoing technical support (78% of participants), underscoring the need for infrastructure development and sustained assistance programs. This experience demonstrates that targeted capacity-building interventions can effectively bridge the digital divide for rural enterprises when combined with local partnership approaches.